Reconstructing Criminal Liability Models for the Dissemination of False Information in the Indonesian Criminal Justice System : An Analysis of the ITE Law After the 2024 Amendment - Nabil Librian Pratama; R Arif Sulaiman (Manunggal Halim Jaya, 2026)
This study analyzes and reconstructs the model of criminal liability for the dissemination of false information in the Indonesian criminal law system, particularly based on the provisions of the Electronic Information and Transactions Law after the 2024 amendment. Despite the increasing regulation of false information under the ITE Law, there remains a lack of clarity regarding the conceptual boundaries and application of criminal liability, as well as limited scholarly discussion on how such liability should be reconstructed to balance law enforcement and freedom of expression. This study addresses this research gap by offering a systematic reconstruction model. This study employs a normative legal approach using legislative and conceptual methods, analyzed descriptively and prescriptively through a structured literature review. The findings show that criminal liability for the dissemination of false information requires the fulfillment of the elements of criminal acts (actus reus) and fault (mens rea), which are reflected in the elements of “intentionally” and “without rights” in the ITE Law. However, in practice, there is still uncertainty regarding the definition of “false information,” the potential for multiple interpretations, and the risk of excessive criminalization that could conflict with freedom of expression. These issues indicate a gap between normative regulation and its practical implementation. Therefore, the reconstruction model emphasizes (1) clear and restrictive definitions of false information, (2) strict proof of intent, (3) application of proportionality in criminal sanctions, and (4) differentiation of roles between content creators, redistributors, and electronic system operators. This model places criminal law as the ultimum remedium to ensure legal certainty, justice, and effective protection of freedom of expression in the digital space.